Digital Transformation in Business Marketing of SMEs in Celuk Village, Gianyar, Bali - Krismajayanti, Ni Putu Ari; Nurmalasari, Made Ratih; Prawitasari, Putu Putri; Megawati, Ida Ayu Putu (Jurnal Pengabdian Masyarakat, 2025)
Purpose: The aim of the research paper is to provide education and direct practice with SMEs in Celuk Village, Sukawati. Simple digital marketing by using Linktree. An application that integrates all platforms owned by business actors. Method: The study aims to enhance SMEs knowledge and abilities in product marketing by employing socialization, training, and mentoring. Practical Application: The research provides important insights into SMEs in Celuk Village, Gianyar, Bali to boost their marketing. By investing in training and mentoring digital marketing, that can enhance their marketing effectiveness and overall business performance. Conclusion: This study highlights the importance of improving the use of digital marketing. It offers practical steps for SMEs to enhance their marketing strategies and stresses the need to adapt to digital trends to maintain long-term competitiveness.